Conservation and promotion of the cultural heritage value of Binh Thuy communal house in the development of cultural tourism in Can Tho City - Lộc, Tăng Tấn (Edelweiss Applied Science and Technology, 2025)
This paper investigates the cultural heritage values of Binh Thuy Communal House - a representative spiritual-architectural monument in Can Tho - and proposes strategies for its preservation in conjunction with sustainable cultural tourism development. The study aims to clarify the role of Binh Thuy Communal House in shaping local cultural identity and leveraging its tourism potential amid urbanization and digital transformation. An interdisciplinary approach was employed, combining fieldwork, sociological surveys, and historical document analysis. Findings reveal that Binh Thuy Communal House possesses significant architectural and spiritual value and serves as a highly attractive destination for both domestic and international tourists. The study recommends solutions such as digitizing heritage information, developing experiential tourism products, and enhancing digital communication. It concludes that Binh Thuy Communal House holds a pivotal position in Can Tho’s cultural tourism development strategy. The practical significance lies in providing a scientific basis and policy suggestions for heritage conservation linked to local socio-economic development.